Association of Left Atrial Function Index with Atrial Fibrillation and Cardiovascular Disease: The Framingham Offspring Study. Issue 7 (30th March 2018) - Sardana, Mayank; Lessard, Darleen; Tsao, Connie W.; Parikh, Nisha I.; Barton, Bruce A.; Nah, Gregory; Thomas, Randell C.; Cheng, Susan; Schiller, Nelson B.; Aragam, Jayashri R.; Mitchell, Gary F.; Vaze, Aditya; et al.
Abstract : Background: Left atrial (LA) size, a marker of atrial structural remodeling, is associated with increased risk for atrial fibrillation (AF) and cardiovascular disease (CVD). LA function may also relate to AF and CVD, irrespective of LA structure. We tested the hypothesis that LA function index (LAFI), an echocardiographic index of LA structure and function, may better characterize adverse LA remodeling and predict incident AF and CVD than existing measures. Methods and Results: In 1786 Framingham Offspring Study eighth examination participants (mean age, 66±9 years; 53% women), we related LA diameter and LAFI (derived from the LA emptying fraction, left ventricular outflow tract velocity time integral, and indexed maximal LA volume) to incidence of AF and CVD on follow‐up. Over a median follow‐up of 8.3 years (range, 7.5–9.1 years), 145 participants developed AF and 139 developed CVD. Mean LAFI was 34.5±12.7. In adjusted Cox regression models, lower LAFI was associated with higher risk of incident AF (hazard ratio=3.83, 95% confidence interval=2.23–6.59, lowest [Q1] compared with highest [Q4] LAFI quartile) and over 2‐fold higher risk of incident CVD (hazard ratio=2.20, 95% confidence interval=1.32–3.68, Q1 versus Q4). Addition of LAFI, indexed maximum LA volume, or LA diameter to prediction models for AF or CVD did not significantly improve model discrimination for either outcome. Conclusions: In our prospective investigation of a moderate‐sized community‐based sample, LAFI, a composite measure of LA size and function, was associated with incident AF and CVD. Addition of LAFI to the risk prediction models for AF or CVD, however, did not significantly improve their performance.